Why Disclosure Regimes Fail to Produce Accountability: A Theory of Transparency Architecture - Amanda Reid (Science, Technology & Public Policy, 2026)
Contemporary governance regimes rely on disclosure mandates to render complex organizations accountable, yet the expansion of transparency reporting in platform governance, financial markets, and environmental policy has produced no commensurate expansion in oversight capacity. This persistent gap between disclosure volume and accountability motivates the present study. This Article argues that the gap arises because prevailing approaches misspecify transparency as a binary or scalar property, obscuring a structural problem: the systematic decoupling of disclosure breadth, informational resolution, and reporting institutionalization. This misspecification is not incidental but structural, since the measurement frameworks used to evaluate transparency actively incentivize the failure modes they are designed to detect. To address this problem, the Article develops a general theory of transparency architecture failure and proposes the Transparency Architecture Typology, which disaggregates transparency into three analytically distinct dimensions and identifies the mechanisms (compliance optimization, template rigidity, and informational cost asymmetry) that systematically drive disclosure regimes toward formally compliant but informationally inadequate configurations. From this framework, six theoretical propositions are derived, each specifying falsifiable conditions that anchor an empirical research program. The account is grounded in illustrative evidence drawn from platform disclosure episodes and financial reporting, which confirms that the framework’s structural predictions correspond to identifiable patterns in the observable record. The Article concludes by reframing transparency as an epistemic design problem and by specifying the architectural conditions under which disclosure can generate the informational basis that accountability requires, with direct implications for the design of mandatory disclosure regimes such as the European Union’s Digital Services Act.